Molecular diagnosis of an unconventional 5'splice site mutation causing congenital liver fibrosis - Muhammad Ridhwan Mohammad Muzaki (2016)
Normally, disease-causing 5′ splice-site (5′ss) mutations disrupt Watson-Crick/wobble base pair(s) with U1 small nuclear RNA (snRNA) but some mutations do not. In this thesis, we investigated a T→C mutation in hemochromatosis (HFE) intron 2 which might break a possible non-canonical Ψ-U base pair in 5′ss recognition. This mutation occurs in cis with a c.193A→T HFE exon 2 mutation in a patient with hereditary hemochromatosis (HH). HFE exon 2 encodes for the protein domain that interacts with Transferrin receptor 1 (TFR1), so disrupting this interaction by removing this domain should cause hemochromatosis. To characterize the effects of these nucleotide substitutions on exon 2 inclusion, we constructed a HFE splicing minigene and introduced these mutations. After mammalian cell transfection, the splicing patterns were inferred by RT-PCR and gel electrophoresis. Surprisingly, the T→C mutation slightly enhanced exon 2 inclusion while the c.193A→T mutation caused significant exon 2 skipping. Thus, our findings have shown that the T→C mutation is not likely causing HH while the c.193A→T mutation contributes to HH by disrupting an exonic splicing enhancer (ESE) which induces exon skipping. As the c.193A→T mutation is generally only linked to mild hemochromatosis, further work is required to identify other HH-causing mutations in this patient.